Co-occurrence of NDM-5, OXA-181, and CMY-2 in a Clinical E. coli Isolate From a Patient in the United States. (4th October 2017) - Miller, William; Rios, Rafael; Diaz, Lorena; Panesso, Diana; Chang, Michael; Sun, Zhizeng; Palzkill, Timothy; Arias, Cesar
Abstract: Background: Carbapenem-resistant Enterobacteriacae (CRE) are an important public health problem. A mechanism of expansion of the CRE epidemic is transcontinental spread of multidrug-resistant organisms. Here, we present a patient with an intra-abdominal abscess due to Escherichia coli with an unusual multidrug resistance phenotype who was admitted to a tertiary hospital in Houston, TX after treatment in a country from the Middle East. Methods: Identification and antimicrobial susceptibility testing were performed by standard methods. Whole-genome sequencing (WGS) was performed on an Illumina platform, with resistance genes identified by ResFinder 2.1 and plasmids recognized using PlasmidFinder 1.3. Results. It is confirmed via PCR, S1 pulsed field gel electrophoresis, and Southern blotting. Carbapenemase activity of bacterial lysates was assayed using 50 µM imipenem in the presence of both EDTA and zinc. Results: The E. coli isolate was resistant to all β-lactams, including ceftazidime/avibactam. The organism belonged to ST410 and harbored bla NDM-5, bla OXA-181, bla CMY-2, and bla TEM-1B . The bla OXA-181 gene was located on an IncX3 plasmid of ca. 50 Kb in association with the IS Ecp1 mobile element and the qnrS21 gene encoding quinolone resistance. The bla NDM-5 gene was located on an FIA/FIB plasmid of 100 Kb, in association with ΔIS Aba125, and upstream of a putative bleomycin resistance gene, a conserved arrangement among NDM expressing Gram-negative organisms. Cell lysate assays showed decreasing carbapenemase activity with increasing concentrations of EDTA and an increase in activity with the addition of zinc, suggesting the NDM-5 metallo-β-lactamase is largely responsible for the observed carbapenemase activity. Comparison with plasmid sequences available suggested convergence of resistance determinants captured from a wide geographic area. Conclusion: Plasmid-mediated spread of β-lactamases among Enterobacteriaceae is a rapidly evolving threat, with the introduction of NDM-5 and OXA-181 in the United States being a particularly disturbing development. Introduction of multidrug-resistant organisms from areas of high prevalence of resistance may change the landscape of antimicrobial resistance in the United States. Disclosures: All authors: No reported disclosures.